Can sector-specific REIT strategies outperform a diversified benchmark?. Issue 3 (6th November 2017) - Moss, Alex; Clare, Andrew; Thomas, Stephen; Seaton, James
Abstract : Purpose: The authors in this paper aim to investigate the performance of different portfolios of REITs which specialise by property type compared to the performance of a diversified free-float market capitalisation-weighted benchmark index to determine whether superior risk-adjusted returns can be achieved. Design/methodology/approach: First, the authors examine the performance of portfolios constructed using the criteria of equal weight, minimum variance, maximum Sharpe and risk parity rather than free-float market capitalisation. Second, the authors apply an automated trading strategy of trend following to see if this filter will improve risk-adjusted returns. Findings: The two-step process of forming combinations of REIT sectors with the subsequent addition of a trend following overlay can offer clear benefits relative to a passive benchmark investment. Research limitations/implications: Although three of the four strategies were shown to outperform the benchmark index on a risk-adjusted basis, one issue was that the efficient portfolios tended to have large weightings to relatively few sectors. The authors also found that maximum drawdowns (losses) of the strategies tended to be rather high, as was the benchmark. Practical implications: The methods outlined in this paper can be applied to construct superior risk-adjusted REIT portfolios globally. Originality/value: Although studies have been undertaken separately on REIT specialisation and trend following in equity and commodity markets, this paper is the first to combine the two topics, and therefore has particular value for real estate fund managers globally.